Development of Android-based Interactive Multimedia to Enhance Critical Thinking Skills in Learning Matters - Salma Almira Hamdani; Eka Cahya Prima; Rika Rafikah Agustin; Selly Feranie; Ahmad Sugiana (Journal of Science Learning, 2022)
The advancement in science and technology in the 21st Century necessitates improving critical thinking skills in students. Implementing digital technology such as interactive multimedia in the learning process can encourage quality learning and teaching. This study aims to create Android-based interactive multimedia that will help students improve their critical thinking skills in learning matters. This research aims to develop android-based interactive multimedia to enhance critical thinking skills in learning matters. This research employed a developmental method that included analysis, design, development, implementation, and one group pretest-posttest to assess students' critical thinking skills. The participants were 30 students from Private Junior High schools in Bandung Barat. The instruments used were the expert's judgment rubric, students' questionnaire, and objective test. With an overall score of 88.25%, the experts' judgment score was classified as very good. Moreover, the average score of students' impressions was 84.56%, classified as very good. Based on the data analysis, the value of g is 0.52, which is classified as a medium enhancement. This finding indicates that students' critical thinking skills improve after applying Android-based interactive multimedia.